Margaret Chase Smith Essay: Priorities of the U.S. Senate Aging Committee - Collins, Susan (Maine Policy Review, 2015)
Senator Susan Collins of Maine discusses the three major priorities of the U.S. Senate Aging Committee: investing in biomedical research targeting diseases that disproportionately affect older Americans, such as Alzheimer’s and diabetes; protecting seniors against financial exploitation and scams; and improving retirement security.